Systematic review and meta-analysis of mortality in crop protection product manufacturing workers. Issue 1 (18th December 2008) - Jones, D R; Sutton, A J; Abrams, K R; Fenty, J; Warren, F; Rushton, L
Abstract : Objectives: The potential health effects of the manufacture and use of crop protection chemicals were investigated through systematic review and meta-analysis of studies of cohorts of workers in the crop protection product manufacturing industry. Methods: Several computerised literature databases were searched from inception until December 2003, with references listed in identified articles checked for further relevant articles. Random effects meta-analyses of log standardised mortality ratios (SMRs) were carried out. Heterogeneity was explored through subgroup analyses and meta-regression; sensitivity analyses of different approaches for zero events were performed. Results: 21 references reporting information on 37 separate cohorts for mortality were identified. The meta-SMR for all cause mortality was 0.94 (95% CI 0.88 to 1.00) (37 cohorts). Significantly raised mortality was found for cancers of the buccal cavity and pharynx, oesophagus, rectum, larynx, lung, and lymphatic and haematopoietic system with little heterogeneity being observed. Excluding studies with zero events identified additional excesses. Conclusions: Evidence of multiple excesses, particularly in subgroups exposed to phenoxy herbicides contaminated with dioxins, substantiates previous findings. The importance of careful treatment of zero cases was highlighted. Future systematic reviews and meta-analyses would benefit from availability of results for a standard list of causes of disease.